Improved Performance of Polymer Electrolyte Membrane Fuel Cells with Modified Microporous Layer Structures. Issue 9 (23rd May 2017) - Alrwashdeh, Saad S.; Manke, Ingo; Markötter, Henning; Haußmann, Jan; Arlt, Tobias; Hilger, André; Al‐Falahat, A. M.; Klages, Merle; Scholta, Joachim; Banhart, John
Abstract: A possible method to improve membrane humidity conditions in polymer electrolyte membrane fuel cells and, therefore, the cell performance is the optimization of microporous layer (MPL) structures. In this work, water transport in modified MPL materials in polymer electrolyte membrane fuel cells (PEMFCs) was investigated by in operando synchrotron X‐ray tomography. Three different types of MPLs are compared: A reference standard MPL material, an MPL material with a special wavy structure, and an MPL with randomly distributed holes. We found a strong impact of the modified MPL structure on the water distribution at operating temperatures of 40 and 55 °C and an increase of cell performance up to 14 % compared to the reference cell. We assume the water distribution at the membrane to be responsible for the performance increase and provide a detailed discussion. Abstract : Structural impacts : Three different types of modified microporous layer (MPL) materials are compared: A reference MPL material, an MPL with wavy structure, and an MPL with randomly distributed holes. There is a strong impact of the modified MPL structure on the water distribution at temperatures of 40 and 55 °C and an increase of cell performance compared to the reference cell.